Improved purification procedure and some serological and physical properties of cassava common mosaic virus from South America - Nolt, Barry L.; Velasco, Ana Cecilia; Pineda López, Benjamín (Wiley, 1991)
Large quantities of cassava common mosaic virus (CCMV) were purified from systemically infected Nicotiana benthamiana plants. A polyclonal antiserum, with a titre of 1/128 in the tube precipitin test, was produced by immunising rabbits with purified virus. Viral antigens were detected in cassava, using both the double-antibody sandwich or plate-trapped antigen forms of enzyme-linked immunosorbent assay (ELISA). The virus reacted with antisera to the potexviruses potato virus X and tulip virus X in F(ab`)2 ELISA. As determined by ELISA, isolates of CCMV from cassava and chaya are closely serologically related to each other. Leaf extracts from infected N. benthamiana plants were infective to a dilution of 10(- 4) but not 10(-5); after heating for 10 min at 65 degrees C but not 70 degrees C; and after storage at room temperature for 14 days. The virus has a sedimentation coefficient of 126 S20,w, a single coat protein molecule of c. mol. wt 21 000, and a single-stranded RNA genome of c. mol. wt of 2.0 x 10(6). Several dsRNA species, including the putative viral replicative form of c. mol. wt 4.1 x 10(6), were isolated from virus-infected cassava and N. benthamiana. (AS)